2016
DOI: 10.4238/gmr.15037563
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 -572G/C polymorphism and prostate cancer susceptibility

Abstract: ABSTRACT. Strong evidence suggests that cancer-associated inflammation promotes tumor growth and progression, and interleukin-6 (IL6) is an important modulator of inflammation. However, the roles of IL6 and mutations of its corresponding gene in prostate cancer have not been clearly documented. We retrieved data from the Oncomine database concerning IL6 expression in prostate cancer and its role in prostatespecific antigen (PSA) recurrence. We also performed a case-control study of the IL6 -572G/C polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
1
1
Order By: Relevance
“…Elevated levels of IL6 are typically associated with obesity-related inflammation and type 2 diabetes in adolescents and adults with obesity (2,3). One recent study found higher promoter activity of the rs1800796 G-allele compared with the C-allele (32). Interestingly, in this study, rs1800796-CC homozygotes had lower plasma IL6 levels when compared with G-allele carriers.…”
Section: Discussioncontrasting
confidence: 41%
“…Elevated levels of IL6 are typically associated with obesity-related inflammation and type 2 diabetes in adolescents and adults with obesity (2,3). One recent study found higher promoter activity of the rs1800796 G-allele compared with the C-allele (32). Interestingly, in this study, rs1800796-CC homozygotes had lower plasma IL6 levels when compared with G-allele carriers.…”
Section: Discussioncontrasting
confidence: 41%
“…Jurečekova et al ( 12 ) also observed an increase in IL-6 mRNA expression but did not find any association between the presence of the rs1800795 polymorphism and the alterations of its gene expression. Nevertheless, Huang et al ( 29 ) demonstrated that the presence of the rs1800796 polymorphism is able to modulate the transcriptional activity of the IL-6 gene, resulting in a high risk of prostate cancer. The meta-analysis by Peng et al ( 14 ) showed that the three polymorphisms influence the expression of IL-6 , contributing to the progression of cancer.…”
Section: Discussionmentioning
confidence: 99%